KEDUDUKAN RELAAS PANGGILAN TERHADAP PUTUSAN VERSTEK DI PENGADILAN AGAMA MAKASSAR - Dwi Utami Hudaya Nur (Fakultas Syariah Institut Agama Islam Negeri Palu, 2016)
Relaas summon and verdict are two kinds of court prosesses that are related to and influenced each other. Relaas summon’s position on versteck verdict is considered tremendously pivotal, since summon’s process is the first procedure done prior to proceedings, summoning all the parties to attend at trial is crucial for further proceedings as both of litigants presences will be able to assist the judge in listening the reasons from both sides to considered and decided. Relaas summon, in this case, is one of the most authentic act that will be examined first by a panel of judges in order to see if the bailiff or substitute bailiff have been carrying out the duties and responsibilities properly then the summon has been executed officially and seemly. Thus when the relaas summon has been submitted formally and properly while the defendant still does not present under invalid reasons, and did not send his/her attorney as well to be present at the court then this is where the judge considers to decide the case whether defendant will be called again to be able to attend the hearing or the judge directly examines the plaintiff’s witnesses and then settles the case by verstek verdict.